Blow-up for degenerate nonlinear parabolic problem - Y. Chan, W. (AIMS mathematics, 2019)
In this paper, we deal with the existence, uniqueness, and finite time blow-up of the solution to the degenerate nonlinear parabolic problem: uτ=(ξrumuξ)ξ/ξr + up for 0 < ξ < a, 0 < τ < Γ, u (ξ, 0) = u0 (ξ) for 0 ≤ ξ ≤ a, and u (0, τ) = 0 = u (a, τ) for 0 < τ < Γ, where u0 (ξ) is a positive function and u0 (0) = 0 = u0 (a). In addition, we prove that u exists globally if a is small through constructing a global-exist upper solution, and uτ blows up in a finite time.